309 CREATING A RICH LEARNING AND TEACHING ENVIRONMENT BASED ON THE PRINCIPLES OF ADULT LEARNING TO TEACH EMERGENCY CASE MANAGEMENT TO MEDICAL UNDERGRADUATE STUDENTS WITH USE OF THE HUMAN PATIENT SIMULATOR. (1st January 2005) - Kozmenko, V.; Chauvin, S.; Yang, T.; DiCarlo, R.; Hilton, C.
Abstract : Purpose: LSU School of Medicine developed and implemented an innovative, year-long curriculum for junior medical students using the high fidelity Human Patient Simulator (METI, Inc.). Teaching methods are based on principles of adult learning in student-focused and highly interactive simulation sessions using specific patient scenarios. Methods: Beginning in July 2003, junior medical students on the New Orleans campus participate in a series of eight HPS simulation sessions whose content was identified by the participating clerkship directors (acute thermal injury, gastrointestinal [GI] bleeding, pneumothorax, congestive heart failure [CHF], atrial fibrillation, bronchial asthma attack, septic shock, and eclampsia). Each case represents a modified simulation version of the standard treatment protocol of a given medical condition. Scenarios include simulator's scripted responses to both correct and incorrect interventions that result in successful and unsuccessful outcomes. The model-driven script-controlled responses of the simulator provide immediate feedback to the students based on their interventions. Simulator automatically detects most of the performed interventions and interprets their appropriateness in accordance with scripted protocol. Simulator's feedback provides a mechanism of reinforcement or punishment for correct or incorrect behaviors correspondingly. Instructor enters data of interventions that simulator cannot detect automatically. This approach allows students to integrate active analysis of the patient's status and responses to treatment with synthesis of appropriate clinical algorithm. At the end of the session, the students debrief the case and compare their performances with the standard protocols (PALS, ACLS etc.). Methods: A pre/post test design was used to examine knowledge gains as a measure of curriculum effectiveness. Each scenario-based quiz consisted of ten multiple-choice questions. Results: Complete data were available for pre/post test total scores (n = 599) across the six scenarios for which tests were administered. Post-pre test score differences ranged from 35.49 to 45.18 (p < .0001). Conclusion: The knowledge gains observed for initial implementation of the HPS curriculum are encouraging and supportive of the use of adult learning methods.